Sasi Labuang (Petuanan Negeri) sebagai Bentuk Perlindungan Terhadap Biota Laut Di Negeri Adat - Noya, Ekberth Vallen (Pusat Kajian Pesisir dan Masyarakat Hukum Adat Fakultas Hukum Universitas Pattimura, 2023)
Sasi is a community tradition that has substantive legal value, namely it is a temporary prohibition against taking forest or marine products until a certain time. Sasi can be said to have legal value, because it has norms or rules relating to methods, customs, codes of conduct and customs which contain elements of ethics and norms. All maintenance of natural resources is supervised by traditional institutions such as kings, soa heads, saniri, kewang and marinyo. However, those who play a more important role in maintaining these natural resources are the kewang and the kewang's children who function as forest rangers. Kewang plays an important role, because it is one of the elements of government which is tasked with protecting the environment both on land and at sea from the hands of irresponsible people. Sasi is a tradition that is still well maintained to this day in several existing traditional countries. in Maluku, the same thing happens in Hulaliu country, where sasi still exists, but is used for plant sasi, such as Coconut Tree sasi. In preserving the environment, currently there is a lot of environmental damage due to the actions of irresponsible people. The sasi custom can play a role in preventing this. Sasi is a combination of custom and religion and sasi is also a sacred custom.